PERBEDAAN MOTIVASI, KEPUASAN KERJA, KEINGINAN BERPINDAH KERJA, DAN PERSEPSI DISKRIMINASI ANTARA AUDITOR PRIA DAN WANITA PADA KAP DI KOTA SEMARANG - Pudjowibowo, Caroline (Jurnal Akuntansi Bisnis, 2014)
World of work in this era of globalization, demands high professionalism qualifications to gain employment, regardless of gender. Even now, women have equal rights with men in entering the workforce. Ironically, gender is often at issue in the work environment. The gender problem arises because there is no doubt that there is a fundamental difference between men and women, which then have an impact when they are in a work environment. This study purposes to compare between male and female auditors in terms of the level of motivation, job satisfaction, desire of turnover, and perceptions of discrimination when they are in their work environment. Object of this study is sample of all men and women auditor, who work at the firm in the city of Semarang. The results of this study find that there was no difference in motivation, the desire of turnover, and the perception of discrimination between male and female auditors. However, there were differences in job satisfaction between the two, and the results of this study demonstrate that the level of job satisfactionâs male auditors is higher than female auditors.